Existence and Non-Existence of Positive Solutions for a Discrete Fractional Boundary Value Problem (Journal of Nonlinear Modeling and Analysis, 2024)
In this work, we deal with two-point boundary problem for a finitenabla fractional difference equation. First, we establish an associated Green'sfunction and state some of its properties. Under suitable conditions, we deducethe existence and non-existence of positive solutions to the considered problem.Finally, we construct a few examples to illustrate the established results.